Silent Thyroiditis Presented as Transient Hypothyroidism during Pregnancy: A Case Report - Mahmoud Ali Kaykhaei; Shahin Nosratzehi (Case Reports in Clinical Practice)
Silent thyroiditis during pregnancy is an under-recognized clinical condition and a rare case, often manifesting as transient hypothyroidism. We report a 23-year-old woman at 8 weeks of gestation who presented with newly diagnosed hypothyroidism [TSH = 85 mIU/L (0.4–4.5), FT4 = 0.4 ng/dL (0.7–2.5), and anti-TPO = 78 IU/mL (up to 16)]. Thyroid function tests had been normal eight months prior. Levothyroxine (LT4) therapy was initiated, restoring euthyroidism. Treatment was discontinued postpartum, and the patient maintained normal thyroid function for over one year. Our case is unique in that silent thyroiditis occurred unusually early in pregnancy and differed from the more common postpartum cases. Silent thyroiditis should be considered in pregnancy-related hypothyroidism, particularly when prior thyroid function was normal. Prompt diagnosis and treatment can prevent adverse maternal and fetal outcomes.